Delay-tolerant distributed voltage control for multiple smart loads in AC microgrids. (March 2019) - Lai, Jingang; Lu, Xiaoqing; Tang, Ruo-Li; Li, Xin; Dong, Zhengcheng
Abstract: With increasing penetration of variable loads and intermittent distributed energy resources (DERs) with uncertainty and variability in distribution systems, the power system gradually inherits some features (e.g., lack of rotating inertia), which leads to the voltage instability in microgrids. As a means to provide stability support for smart grid against high penetration of intermittent DERs, inverter-based smart loads across the distribution grid has been suggested recently. Accordingly, this paper presents a delay-tolerant distributed voltage control scheme based on consensus protocol for multiple-cooperative smart loads through effective demand-side management in ac microgrids, in which the time-delay effect on transmission communication occurred in information exchanges is considered. The proposed distributed voltage control scheme always enables the output voltage of each smart load to be synchronized to their reference value, which improves the robustness of system stability against transmission communication delays. The Lyapunov–Krasovskii functions are employed to analyze the stability of our proposed distributed control scheme, then the delay-independent stability conditions are derived, which allows some large communication delays. Moreover, the sensitivity analysis is developed to show how the time delay affects system dynamics in order to validate the robustness of proposed delay-independent stability conditions. Furthermore, a sparse communication network is employed to implement the proposed distributed control protocols, which thus satisfies the plug-and-play requirement of smart microgrids. Finally, the simulation results of an ac microgrid in MATLAB/SimPowerSystems are presented to demonstrate the effectiveness of the proposed control methodology. Highlights: We use smart loads to manage system voltage from demand side other than DER's side. The consensus-based voltage protocol is robust against large communication delays. Lyapunov–Krasovskii-based large-signal stability analysis is given for microgrids. The delay-independent stability condition is derived to simplify its implementation. The fully distributed voltage scheme allows DERs' plug and play or distributed loads.